Pengaruh Pemberian Beberapa Dosis Pupuk NPK dan Komposisi Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Cabai Merah (Capsicum annuum L.) - Nabila, Fitri; Suliansyah, Irfan; Kristina, Nilla (Jurnal Agroekoteknologi, 2024)
Red chilli is a crucial vegetable crop in Indonesia, facing a rising demand that calls for increased production. Enhancements in red chilli production may be achieved by adopting polybag cultivation techniques. This study aims to find the interaction between various NPK fertilizer dosages and planting media compositions on the best growth and yield of red chilli plants and to determine the best NPK fertilizer dosage and plant media composition for the growth and yield of red chilli plants. The research was conducted at the net house, Faculty of Agriculture, Andalas University, from March to August 2023. This investigation was a factorial experiment organized in a Completely Randomized Design (CRD), comprising two factors with three replicates each. The first factor was the dosages of NPK fertilizer: 300, 400, and 500 kg/ha. The second factor concerned the composition of the planting medium, consisting of ultisol soil, cow manure, and cocopeat in ratios of 2:1:1, 2:2:1, and 2:1:2. Data analysis was conducted using the F-test followed by DNMRT at a 5% significance level. The findings indicated no interaction between the dosages of NPK fertilizer and the composition of the planting medium concerning the growth and yield of red chilli plants. The application of NPK fertilizer at a dosage of 400 kg/ha positively influenced the variables of dichotomous branch number and the number of fruits per plant, whereas the planting medium composition of 2:2:1 exerted the most favourable effect on plant height, flowering age, number of fruits per plant, and fruit weight per plant.